Ene-nucleic acids: a different paradigm to DNA chemistry - Varada, Manojkumar; Erande, Namrata D.; Kumar, Vaijayanti A. (RSC Advances, 2015)
Acyclic prochiral nucleic acids such as FNA, UNA, GNA and cyclic chiral TNA are all considered as precursors of DNA and RNA in the chemical etiology of nucleic acids. The chemical reasoning would suggest that unsaturated precursors with constrained flexibility and selectivity based on cis/trans isomers could be the missing link between the prochiral-acyclic and chiral-cyclic structures mentioned above. We find that ene-nucleic acids derived from an isoprenoid skeleton possess requisite flexibility and rigidity while forming stable duplex structures with complementary DNA and RNA.